(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
In this work we strive to frame the full space of cloud-computing security issues, attempting to separate justified concerns from possible over-reactions. We examine contemporary and historical perspectives from industry, academia, government, and â€œblack hatsâ€. We argue that few cloud computing security issues are fundamentally new or fundamentally intractable; often what appears â€œnewâ€ is so only relative to â€œtraditionalâ€ computing of the past several years. Looking back further to the time-sharing era, many of these problems already received attention. On the other hand, we argue that two facets are to some degree new and fundamental to cloud computing: the complexities of multi-party trust considerations, and the ensuing need for mutual audit ability. Â